Penerapan Model Pembelajaran REACT untuk Meningkatkan Pemahaman Konsep Peserta Didik pada Pokok Bahasan Termokimia di Kelas XI SMA - Pidi Septianti; Susilawati Susilawati (Al-DYAS, 2026)
Students’ conceptual understanding of chemistry, particularly on the topic of thermochemistry, remains relatively low despite the implementation of student-centered learning. This condition indicates the need for alternative learning that can connect chemistry concepts with real-life experiences and increase students’ active engagement. This study aims to analyze the effect of implementing the REACT (Relating, Experiencing, Applying, Cooperating, Transferring) learning model on students’ conceptual understanding of thermochemistry. This study used an experimental method with a Randomized Control Group Pretest–Posttest design in two Grade XI classes at SMAN 4 Pekanbaru in the 2025/2026 academic year. Class XI 6 as the experimental class received REACT learning, whereas class XI 7 as the control class received learning using a scientific approach. The data were analyzed using normality tests, homogeneity tests, t-tests, and N-Gain. The results showed a significant difference between the experimental class and the control class, with a calculated t-value of 6.47 > table t-value of 1.66 at a significance level of 0.05. The N-Gain score of the experimental class was 0.85 in the high category, higher than that of the control class, which was 0.69 in the moderate category. Improvements also occurred in all indicators of conceptual understanding. The conclusion of this study affirms that the REACT learning model is effective in improving students’ conceptual understanding of thermochemistry. The implications of this study indicate that REACT-based contextual learning can be used as an alternative chemistry learning strategy to improve the quality of students’ conceptual understanding and learning outcomes.